The Study of Employee Engagement Antecedents and the Effect on Organizational Commitment Hospitals in Banten - Heri Sapari Kahpi; Fathurrohman Fathurrohman; Mirza Abdi Khairusy; Fidziah Fidziah; Didi Wandi (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
This study aims to analyze the effect of perceived organizational support on organizational commitment mediated by employee engagement in hospitals in Banten. Data were collected from one hospital in Banten, and samples were taken using google form totaling 65 respondents. The sampling technique in the study used random proposal sapling. The results of this study indicate that perceived organizational support has a positive direct effect on organizational commitment, perceived organizational support has a direct positive effect on employee engagement, employee engagement has a positive direct effect on organizational commitment, and perceived organizational support has an indirect effect on organizational commitment and is mediated by employee engagement.